2015
DOI: 10.1037/xap0000033
|View full text |Cite
|
Sign up to set email alerts
|

Believing in “us”: Exploring leaders’ capacity to enhance team confidence and performance by building a sense of shared social identity.

Abstract: The present study examined the impact of athlete leaders' perceived confidence on their teammates' confidence and performance. Male basketball players (N = 102) participated in groups of 4. To manipulate leaders' team confidence, the appointed athlete leader of each newly formed basketball team (a confederate) expressed either high or low team confidence. The results revealed an effect of team confidence contagion such that team members had greater team confidence when the leader expressed high (rather than lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
142
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(164 citation statements)
references
References 59 publications
20
142
2
Order By: Relevance
“…These results support previous research demonstrating a positive impact of athlete leaders on their teammates' team confidence (Bandura, 1997;Fransen, Haslam, et al, 2014;Fransen et al, 2012;Hoyt et al, 2003;Ronglan, 2007). Furthermore, our results again support the previous finding that the task leader is perceived as the most important leader by players and coaches .…”
Section: Discussionsupporting
confidence: 82%
“…These results support previous research demonstrating a positive impact of athlete leaders on their teammates' team confidence (Bandura, 1997;Fransen, Haslam, et al, 2014;Fransen et al, 2012;Hoyt et al, 2003;Ronglan, 2007). Furthermore, our results again support the previous finding that the task leader is perceived as the most important leader by players and coaches .…”
Section: Discussionsupporting
confidence: 82%
“…Third, at the item level (i.e., when looking at the individual sources instead of at the overarching factors), the expression of team confidence by leader figures within the team (i.e., athlete leaders) emerged as the most important source of athletes' and coaches' team outcome confidence. These findings corroborate previous research indicating the important role of athlete leaders in affecting teammates' team confidence (1,10,12,28,38).…”
supporting
confidence: 93%
“…Thus, to the extent that leaders act in the interests of the group (with all other variables held constant), they are indeed perceived to be more charismatic [151,152], as well as more trustworthy [153] and effective [154]. Thus, rather than simply trying to identify the "special stuff" that makes leaders and coaches great, a social identity approach to leadership focuses on the processes through which leaders and followers come to see each other as part of a common ingroup [90,152].…”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
“…Relatedly, experimental research has shown that, because it enhances team members' social identification, the confidence leaders express in a team is a powerful determinant of basketball players' success in competition [90](see also [157]). …”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%
See 1 more Smart Citation